Study of the Smoke Propagation in a Road Tunnel (Journal of Scientific Research, 2013)
Road tunnels are increasingly built due to heavy traffic in dense urban areas. Knowledge of the spread of smoke is still limited. A numerical study on the smoke flow in a tunnel has been made using the model of small-scale tunnel. Effects of the longitudinal air flow on the flow structure, the temperature distribution and the smoke stratification of the fire in the tunnel have been considered by taking into account the inclination of the tunnel and the transverse positioning of the source. The results show that the spread of smoke is independent of the transverse position of the source in the fourth phase of the flow. The slope has a slight influence on the flow and promotes the flow stratification in a ascending slope. The longitudinal air flow promotes destratification of the smoke flow. The model was validated by comparison with experimental data obtained from fire tests (Wu et al.) in a small-scale tunnel.  Keywords: Tunnel fire; Smoke flow; Stratification; FDS  © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.  doi: http://dx.doi.org/10.3329/jsr.v6i1.14696 J. Sci. Res. 6 (1), 51-68 (2014)